2015
DOI: 10.1016/j.bpj.2015.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1 Motors Can Circumvent Permanent Roadblocks by Side-Shifting to Neighboring Protofilaments

Abstract: Obstacles on the surface of microtubules can lead to defective cargo transport, proposed to play a role in neurological diseases such as Alzheimer's. However, little is known about how motor proteins, which follow individual microtubule protofilaments (such as kinesin-1), deal with obstacles on the molecular level. Here, we used rigor-binding mutants of kinesin-1 as roadblocks to permanently obstruct individual microtubule binding sites and studied the movement of individual kinesin-1 motors by single-molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 35 publications
12
74
2
Order By: Relevance
“…In summary, because we observed kinesins which travel with persistently different mean velocities on the same MT (Figure , Movies S2 to S5), and the frequency of velocity groups can be affected by glycerol and temperature as well as pH, we believe that the functional heterogeneity is intrinsic to the motors themselves, not caused by the heterogeneity in MTs or roadblocks on them . Instead, single motors appear to have relatively well defined—but different—mean stepping rates.…”
Section: Discussionmentioning
confidence: 67%
“…In summary, because we observed kinesins which travel with persistently different mean velocities on the same MT (Figure , Movies S2 to S5), and the frequency of velocity groups can be affected by glycerol and temperature as well as pH, we believe that the functional heterogeneity is intrinsic to the motors themselves, not caused by the heterogeneity in MTs or roadblocks on them . Instead, single motors appear to have relatively well defined—but different—mean stepping rates.…”
Section: Discussionmentioning
confidence: 67%
“…For example, the direct comparison between kinesin‐1 and kinesin‐2 motors showed that Tau, a MAP known to heavily decorate axonal microtubules in vivo , affected kinesin‐1's but not kinesin‐2's processivity in vitro . Even though kinesin‐1 can also overcome permanent obstacles in vitro , kinesin‐2 appears to do so more efficiently via its higher propensity to switch protofilaments when compared to kinesin‐1 .…”
Section: Resultsmentioning
confidence: 99%
“…Attachment of nanoparticle labels to kinesin, myosin, and dynein motors has to date been achieved via biotin–streptavidin chemistry (Andrecka et al, 2015; Dunn & Spudich, 2007; Isojima, Iino, Niitani, Noji, & Tomishige, 2016; Mickolajczyk et al, 2015; Schneider, Glaser, Berndt, & Diez, 2013; Schneider, Korten, Walter, & Diez, 2015). One method of introducing biotin into kinesin is to create a cysteine-lite mutant, in which solvent-exposed cysteines are mutated out of the motor domain and a single cysteine is kept to take advantage of sulfhydryl chemistry for attaching a maleimide-functionalized label.…”
Section: Methods and Protocolsmentioning
confidence: 99%